Analisis Saluran dan Marjin Pemasaran Gula Pasir Milik Petani di Kecamatan Gedeg Mojokerto Jawa Timur - Suswatiningsih, Tri Endar; Maryana, Erwin; Ambarsari, Arum (Department of Agribusiness, Halu Oleo University, 2021)
This study analyzes the marketing channels and efficient distribution channels carried out by farmers in marketing sugar products to consumers, knowing how the most economically efficient distribution channels and the obstacles faced by each distribution institution. The essentials primary method used in this research was descriptive. Determination of the location of the study was done purposively. Farmer samples were taken by simple random sampling, and the example of traders was taken by snowball sampling. The entire selection was 28 famers and eight merchants. The research was conducted in May 2018. Data analyzes by calculating the marketing margin and efficiency of each marketing channel. This study indicates that farmers chose four distribution channels to distribute the sugar they have to consumers. The most economically efficient distribution channel was distribution channel III, with an IDR 7,61/kg marketing efficiency value and a marketing margin was IDR 1.000/kg.